2023
DOI: 10.1039/d3sc00228d
|View full text |Cite
|
Sign up to set email alerts
|

CO2-switchable emulsions with controllable size and viscosity

Abstract: CO2-responsive emulsions have attracted considerable attention in recent years because of their biocompatibilities and easy removal of CO2. However, most CO2-responsive emulsions are only used in stabilization and demulsification processes....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…22 Jiang and co-workers reported the Pickering emulsion co-stabilized by silica nanoparticles and anionic NCOONa, as well as investigated its CO 2 -triggered reversible switching of emulsification/breaking states. 23 Zhang and co-workers reported that stimuli-responsive Pickering emulsifiers were prepared by in situ modification of poly(ethylene oxide)− poly(propylene oxide)−poly(ethylene oxide) (PEO−PPO− PEO) on the surface of silica nanoparticles for stabilizing Pickering emulsions, and the pH-and temperature-stimulated response behaviors of the emulsions were systematically investigated. 24 San and co-workers reported that ASCL@ CaCO 3 was prepared by immobilizing sodium-conjugated linoleate (ASCL) on the surface of CaCO 3 nanoparticles to stabilize liquid paraffin emulsions as particle emulsifiers and investigated the stimulus response behavior of the emulsions under the triple trigger of Ca 2+ /pH/CO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Jiang and co-workers reported the Pickering emulsion co-stabilized by silica nanoparticles and anionic NCOONa, as well as investigated its CO 2 -triggered reversible switching of emulsification/breaking states. 23 Zhang and co-workers reported that stimuli-responsive Pickering emulsifiers were prepared by in situ modification of poly(ethylene oxide)− poly(propylene oxide)−poly(ethylene oxide) (PEO−PPO− PEO) on the surface of silica nanoparticles for stabilizing Pickering emulsions, and the pH-and temperature-stimulated response behaviors of the emulsions were systematically investigated. 24 San and co-workers reported that ASCL@ CaCO 3 was prepared by immobilizing sodium-conjugated linoleate (ASCL) on the surface of CaCO 3 nanoparticles to stabilize liquid paraffin emulsions as particle emulsifiers and investigated the stimulus response behavior of the emulsions under the triple trigger of Ca 2+ /pH/CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Xi et al reported that a layer of pure sodium caseinate (NaCas) coated on the surface of bare SiO 2 particles was used to prepare hybrid nanoparticles with pH-responsive properties as Pickering emulsifiers, and the emulsion steady state changes were investigated under different pH environments . Jiang and co-workers reported the Pickering emulsion co-stabilized by silica nanoparticles and anionic NCOONa, as well as investigated its CO 2 -triggered reversible switching of emulsification/breaking states . Zhang and co-workers reported that stimuli-responsive Pickering emulsifiers were prepared by in situ modification of poly­(ethylene oxide)–poly­(propylene oxide)–poly­(ethylene oxide) (PEO–PPO–PEO) on the surface of silica nanoparticles for stabilizing Pickering emulsions, and the pH- and temperature-stimulated response behaviors of the emulsions were systematically investigated .…”
Section: Introductionmentioning
confidence: 99%